THE DEVELOPMENT OF TAMAN PENJUMLAHAN LEARNING MEDIA ASSESTED ARTICULATE STORYLINE 3 ON ADDITIONAL CONCEPT IN FIRST GRADE OF ELEMENTARY SCHOOL - Anggit Septiani; Meiliana Nurfitriani; Yopa Taupik Saleh (CENDEKIAWAN, 2021)
This study aims to develop and test the effectiveness of the additional media with the aid of articulate storyline 3 on the concept of summation in the first grade of SDN II Linggasirna. The method used is the method of developing R&D (Research and Development) Sugiyono. The product trial in this study includes three stages, namely one-on-one trials conducted on 3 students, small group trials conducted on 7 students, and large group trials conducted on 20 students. The data analysis technique used in this research is qualitative and quantitative data analysis. Data collection techniques using a questionnaire and pretest-posttest. The results of the study show that the development of the addition garden media with the help of articulate storyline 3 on the concept of addition is already valid. The results of the pretest and posttest were calculated using the paired sample T-Test analysis technique, the results obtained were count > table or 12,665 > 2,093, which means Ho is rejected and Ha is accepted, meaning that there is a significant difference between before and after being given treatment using the media garden summation assisted by articulate storyline 3 on the concept of summation in the first grade of SDN II Linggasirna. Based on the average results, the posttest value of 87.30 is greater than the pretest of 66.05. Then the addition garden learning media assisted by articulate storyline 3 can be said to be feasible and effective to use in the concept of addition.